Enterpreneur Government Di Desa Manyampa Kecamatan Ujung Loe Kabupaten Bulukumba - Tandi, Asri; Fatmawati, Fatmawati; Rahmawati, Sitti (Universitas Muhammadiyah Makassar, 2021)
This study aimed to how capable village government its integrity as a pioneer in the implementation of government that think creatively, innovatively and professinally in order to realize a good village government independently. This study used a qualitative descrivtove method. Data collection techniques were observation and documentation for describing and analyzing village government as enterpreneurs. The results of this study showed that the enterpreneur government in Manyampa village was seen from the aspects (1) A market-oriented government was initialized but in its implementation not maximized, in developing village enterpreneur government. Village government was not analyzed and observed the conditions on the market at implementation of enterpreneur that he pioneered. (2) Competitive government already run well but needed to increase cooperation from various parties in use support the current enterpreneurship. (3) Results-oriented government, it was still necessary to improve the professional attitude of work in developing enterpreneurship and needed to be aware of all element of village government in the improvement original village income. Keywords : enterpreneurial government, village.